The Role of Co-Parenting on Preschool Children’s Problem Behaviors: The Chain-Mediating Influence of Maternal Parenting Burnout and Psychological Aggression - Qiao, Tianqi; Wang, Xinxin; Ye, Pingzhi; Chang, Jingyi; Huang, Xiuzhen; Wang, Liqun (Current Progress in Arts and Social Studies Research Vol. 3, 2024)
Background and Objective: Recently, the co-parenting system, which involves the father, mother, and child as a unique subsystem within the family system, has garnered significant attention. With the social changes, a growing number of women have joined the workforce, leading to a shift in the traditional roles of child-rearing. There has been a growing focus on the significance of fathers’ roles in child development, particularly the influence of fathers on children's problematic behaviors, making it an increasingly prominent issue. However, there is limited understanding regarding the potential mechanisms through which fathers may exert influence on children’s problem behaviors. To address this gap, this study sought to investigate the link between paternal co-parenting and preschool children’s problem behaviors, and the mediating effects of maternal parenting burnout and psychological aggression. Methods: This is a cross-sectional study and data were collected using the convenience sampling method. This study used the Personal Information Form and four scales to administer questionnaires to 1164 mothers of preschool children (Mage = 4.26 ± 0.85) in Guangdong Province, China. The collected data underwent processing and analysis using SPSS 22.0. Results: All data in this study were obtained through self-reported questionnaires, potentially leading to common method biases influencing the results. The result revealed that paternal co-parenting has a significant influence on the problem behaviors among preschool children. The contribution of paternal co-parenting on children’s problem behaviors was mediated by maternal parenting burnout, maternal psychological aggression, and the combined effect of maternal parenting burnout and psychological aggression. Conclusion: Maternal parenting burnout and maternal psychological aggression play a sequential mediating role between paternal co-parenting and problem behaviors among preschool children. This study revealed the internal mechanism through which paternal co-parenting influenced problem behaviors exhibited by children. It provides some evidence to support the important role of fathers in child development and provides a reference for policymakers and educators to develop interventions for children’s problem behaviors. For a more comprehensive description of the effects of family factors on children’s problem behaviors, future studies can include other family factors for analysis, such as parental psychological control, physical aggression, and other factors.